2017
DOI: 10.1002/hbm.23536
|View full text |Cite
|
Sign up to set email alerts
|

Toward the automatic quantification of in utero brain development in 3D structural MRI: A review

Abstract: Investigating the human brain in utero is important for researchers and clinicians seeking to understand early neurodevelopmental processes. With the advent of fast magnetic resonance imaging (MRI) techniques and the development of motion correction algorithms to obtain high-quality 3D images of the fetal brain, it is now possible to gain more insight into the ongoing maturational processes in the brain. In this article, we present a review of the major building blocks of the pipeline toward performing quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 107 publications
(285 reference statements)
1
26
0
Order By: Relevance
“…This result corresponds well to the asymmetric development of the fetal cortical surface. Several studies have reported the area of the right STS is larger and deeper than the left STS from 26 GW to 30 GW (Benkarim et al, ; Clouchoux, Du Plessis, et al, ; Dubois et al, ; Dubois & Dehaene‐Lambertz, ; Habas et al, ; Kasprian et al, ), and even in term‐born infants (Li et al, ). These results are in line with our findings where the region around the right STS is larger than the region around the left STS, and the growth rate of the right posterior temporal region is higher than the left posterior temporal region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result corresponds well to the asymmetric development of the fetal cortical surface. Several studies have reported the area of the right STS is larger and deeper than the left STS from 26 GW to 30 GW (Benkarim et al, ; Clouchoux, Du Plessis, et al, ; Dubois et al, ; Dubois & Dehaene‐Lambertz, ; Habas et al, ; Kasprian et al, ), and even in term‐born infants (Li et al, ). These results are in line with our findings where the region around the right STS is larger than the region around the left STS, and the growth rate of the right posterior temporal region is higher than the left posterior temporal region.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the medial occipital region of the fetal brain also exhibits an early asymmetry. Beginning at 24 GW, the parieto‐occipital sulcus is more concave on the right than the left hemisphere, and the difference becomes statistically significant after 26 GW (Benkarim et al, ; Habas et al, ). This is consistent with our finding that the right occipital and precuneus cluster is larger than the left occipital and precuneus cluster, and presents larger growth percentage than that on the left hemisphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, segmentation is widely used as basic image quantification step in studies of early brain development (Benkarim et al, 2017) and dementia (Chupin et al, 2009; Li et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…First, sulcal-gyral folding patterns are actually poorly corresponding with the boundaries defined by microstructure, function and development [3]. Second, primary and secondary cortical folds are not well established and are still developing rapidly in the fetal brain [4, 5], as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%